Consumers' ambiguous perceptions of advertising disclosures in influencer marketing: Disentangling the effects on current and future social media engagement - Adrian Waltenrath (Electronic Markets, 2024)
Based on a large real-world dataset comprising Instagram posts of popular influencers, this study empirically analyzes the impact of disclosed and undisclosed advertising on consumers' engagement with (a) the advertisement and (b) future non-advertising posts of the same author. As extant research reports inconsistent effects of ad disclosures based on inferred motives, persuasion knowledge, and source credibility, this study develops a conceptual framework incorporating these theoretical concepts. To identify undisclosed advertisements, we use data from regions with proper disclosure culture to train a model to predict if posts are advertising. Based on the predictions for >~65,000 posts of 239 macro-influencers, we find that advertising posts gather less engagement than non-advertising posts. Regarding immediate ad engagement, we find that disclosed ads gather less engagement than undisclosed ads. Contrastingly, when analyzing future engagement, we identify positive persistent effects of disclosed advertising and negative persistent effects of undisclosed advertising on consumers' engagement with future posts of the same author. We conclude that source credibility explains the effect of disclosures on future posts, while the Persuasion Knowledge Model can explain the effect of disclosures on the current advertisement. Thus, consumers' coping strategies triggered by activated persuasion knowledge are mostly limited to the advertisement. Our findings can explain the opposing results of extant research. From a managerial perspective, we find that by not disclosing advertising posts, influencers and marketers increase an ad's engagement levels at the expense of persistently lowered attitudes. Conversely, in the long run, they may benefit from transparent disclosures.
Keywords: M37; M31; D91; D12; 620; Sponsorship disclosures; Persuasion knowledge; Source credibility; Inferred motives; Consumer attitudes; Transparency